EVALUASI PENERAPAN PROGRAM RINGKAS, RAPI, RESIK, RAWAT, RAJIN (5R) PADA PT. X TAHUN 2020 - Baariq Amjad (2021)
Sort, Set, Shine, Standardize, Sustain (5S) is a program that aims to help companies in creating productivity, efficiency, improving product quality by managing work environment to be clean and tidy, and preventing occupational accidents and work related diseases by implementing 5S program. The majority of the 5S program implementation is applied to manufacturing companies, one of which is PT.X. PT.X has implemented the 5S program since 2014, but there is no increase in program implementation and it is shown by the absence of 5S program implementation reports from 2018-2020. This research aims to evaluate the 5S program implementation at PT.X in 2020. This research uses a descriptive study design with qualitative research methods through in-depth interviews and observations using a checklist form to observe the 5S program implementation. The results showed that the PT.X 5S program implementation was below the basic concept of 5S from the Japan International Cooperation Agency and Unit Pelaksana Pengendalian Pembangkit Bakaru PT PLN implementation standard. Limited building facilities was the cause of poor 5S program implementation at PT.X. Suggestions for the company are to appoint driving force in implementing 5S program and increase new building facilities so that 5S program implementation can run optimally.